Loss of gene function through rapid mitotic cycles in the Drosophila embryo. - Rothe, M.; Pehl, M.; Taubert, H.; Jäckle, H. (Nature, 1992)
The early developmental period in Drosophila is characterized by rapid mitotic divisions, when the body pattern becomes organized by a cascade of segmentation gene activity. During this process localized expression of the gap gene knirps (kni) is required to establish abdomen segmentation. The knirps-related gene (knrl) encodes a kni-homologous nuclear hormone receptor-like protein and shares the spatial patterns of kni expression. The two genes differ with respect to the size of their transcription units; kni contains 1 kilobase and knrl 19 kilobases of intron sequences. The consequence of this difference in intron size is that knrl cannot substitute for kni segmentation function, although it gains this ability when expressed from an intronless transgene. Here we show that the length of mitotic cycles provides a physiological barrier to transcript size, and is therefore a significant factor in controlling developmental gene activity during short 'phenocritical' periods. The required coordination of cycle length and gene size provides severe constraints towards the evolution of rapid development.